Investigation of Water Absorption for Concrete Using Supplementary Materials - Ghewa, Gabriel Jose Posenti; Suprobo, Priyo; Irawan, Djoko; Wahyuniarsih, Sutrisno; Asdam, Tambusay (IPTEK The Journal for Technology and Science, 2025)
Concrete’s durability is the key factor that affects the service life of the concrete structure. One factor that affects the durability properties of concrete is its pore structure, which can be investigated by analyzing the materials’ absorption rate. For the structures with direct contact with water, water absorption can change the pore structure’s behavior, affecting the durability of the conc in the long term rate. It is important to research to find the water absorption properties of concrete with different mixtures. This research investigates the rate of absorption of concrete by using fly ash and silica fume. Based on secondary absorption properties, the result shows that 15% fly ash in normal concrete increases the resistance to water penetration by 23%. The usage of 5% Silica Fume increases the resistance by 11.8%. The usage of 5% silica fume + 10% fly ash increases the resistance by 16.2%. It shows that the use of supplementary materials in concrete increases the resistance of water penetration. In this research, the usage of 15% fly ash as cement replacement shows the best result.